1) a) f(x) = 1 – x

3

f ׳(x) = - 3x
2

=
2
3
2 3
3
1
x
dx
x
− −



=
( )
1
3
2
4
1
3
x C − − +
b)
dV
dt
=10
A = 4πr
2


dA
dr
= 8πr

3
2
4
3
4
V r
dA
r
dr
π
π
=
=


2 1
1
10 2.5
4
dA dV dA
dt dt dV
m s

= ×
= × =

c)

Area= xdy


=
4 2
2
4
2 4
y y
dy

( +

(
¸ ¸


=
4 4
2 3
2 2
1 1
4
2 2 4 3
y y
y
− −
( (
+ −
( (
¸ ¸ ¸ ¸

= 9 unit
2

2. y = x
2
+ 2 ln xy

2
2
dy dy
x x y
dx xy dx
(
= + +
(
¸ ¸


2 2
1 2
dy
x
y dx x
| |
− = +
|
\ ¹


1
2
2
1
x
dy x
dx
y
| |
+
|
\ ¹
=


when x = y =1
4
dy
dx
= −
Further differentiation
2
2
2
1 2ln 2 2ln
d y dy dy
y x
y dx dx dx
| | | |
− + − = +
| |
\ ¹ \ ¹

when x = y = 1
2
2
32
d y
dx
=

3. 6x + 16 = A(2x + 4 ) + B
A= 3, B = 4
6x + 16 = 3( 2x + 4 ) + 4

( )
1
2
2
1
2
2
1 1
2 2
2 2
1
2 1 1
2
2
6 16
4 13
3 2 4 4
4 13
3(2 4) 4
4 13 4 13
1 2
3[ln( 4 13)] 4 tan
3 3
4
3ln 2
3 4
3ln 2
3
x
dx
x x
x
dx
x x
x
dx dx
x x x x
x
x x
π
π


− −



+
=
+ +
+ +
=
+ +
+
= +
+ + + +
+ ( | |
= + + +
| (
\ ¹ ¸ ¸
| |
= +
|
\ ¹
= +


∫ ∫

4. ( )
2
tan sec y x x = +
= ( ) ( )
2
2 tan sec sec tan sec
dy
x x x x x
dx
= + +
=
2 2
2sec 2tan sec tan sec x x x x x ( + +
¸ ¸

= ( )
2
2sec tan sec x x x +

2
cos
dy y
dx x
=
cos 2
dy
x y
dx
= (shown) *
From *
( )
2
2
cos sin 2
d y dy dy
x x
dx dx dx
+ − =
( ) ( ) ( )
3 2 2 2
3 2 2 2
cos sin sin cos 2
d y d y d y dy d y
x x x x
dx dx dx dx dx
(
+ − − − + − =
(
¸ ¸

3 2
3 2
cos cos 2
d y dy d y
x x
dx dx dx
− =
y(0) = 1
y׳(0) = 2
y׳׳(0) = 4
y׳׳׳(0) = 10
f(x) = 1 + 2x + 2x
2
+
5
3
x
3
+ …
4
2
-2
-4
-5 5 10
( )
2
1
8
4
1
4
dA dr dA
dV dV dr
r
r
π
π
= ×
=
=

5. The vertical asymptote, x = -1

2 1
lim
1
1
2
lim
1
1
2
x
x
x
x
x
x
→±∞
→±∞
+
+
+
=
+
=

The horizontal asymptote, y = 2.



when x = 0, y = 1
When y = 0, x = - ½
(0, 1), and ( - ½ , 0 )
Let y =
2 1
1
x
x
+
+

x =
2 1
1
y
y
+
+

y =
1
2
x
x




1
1
: , 2
2
x
f x x
x


∴ → ≠



} {
} {
1
1
: , 2
: , 1
f
f
D x x R x
R y y R y


= ∈ ≠
= ∈ ≠ −


6.
y = e
x

x
dy
e
dx
=
when x = a,
a
dy
e
dx
=
when x = a, y = e
a

The equation of the tangent at the point where x = a is,
y – e
a
= e
a
( x – a )
y = e
a
( 1+x – a )
At (0,0),
e
a
( 1 – a ) = 0
a = 1
The equation of tangent which passes through origin is
y = e ( 1 + x – 1 )
y = ex
For y = mx to intersect y = e
x
at two distinct points, m > e.

7.

( )
( )
0
0
0
( )
ln
ln 27
dx
k x x
dt
dx
kdt
x x
x x kt c
x kt c
= − −
= −

− = − +
− = − +
∫ ∫
When t = 0, x = 63
c = ln36
when t = 6ln 2, x = 45,
k =
1
6

( )
1
6
1
6
1
ln 27 ln36
6
27 36
27 36 ( )
t
t
x t
x e
x proven


− = − +
− =
= +

(a) x – 27
=
7
6
36


= 11.2°C
The fall of temperature after being left in the room for 7
minutes is 11.2°C
(b)
6
36
t
e

= 2

1
6
t
e = 18
t = 6 ln 18
t = 17.3 minutes
The time that elapses is 17.3 minutes.


8. y =
2
25 x −

x 2
25 x −
0 5
0.5 4.9749
1.0
24
1.5
91
4

2.0
21
2.5
75
4

3.0 4
3.5
51
4

4.0 3
4.5
19
4

5.0 0

6
4
2
-2
-4
-5 5
x = - 1
y = - 1
h =
5 0 1
10 2

=

Area = ( )
1 1
5 2 36.30644
2 2
| |
+ (
| ¸ ¸
\ ¹

= 19.40322 unit
2

= 19.4
b) underestimated
c) Area =
5
2
0
25 x dx −


= ( )
2
2
0
5 1 sin 5cos d
π
θ θ θ −


=
2
2
0
25 cos d
π
θ θ


=
2
0
25
(cos 2 1)
2
d
π
θ θ +


=
2
0
25 sin 2
2 2
π
θ
θ
(
+
(
¸ ¸

= 6.25π unit
2


(d)
( )
2 1
5 19.4032
4
3.105
3.11
π
π
π



Master your semester with Scribd & The New York Times

Special offer for students: Only $4.99/month.

Master your semester with Scribd & The New York Times

Cancel anytime.